(untitled) (Avocetta, 2016)
Research on species-habitat relationship implies that a specific parameter related to the species, such as abundance, has to be measured and compared to environmental features. Different methods have been implemented in the collection of abundance data on birds and different statistical techniques have been developed to deal with the great diversity of data collection. The aim of this study is to compare different sampling methods and statistical techniques currently used to estimate abundance, employing them in a dense forest environment: capture-mark-recapture vs. point counts. Short-toed treecreepers Certhia brachydactyla were captured through mist-netting and surveyed through song count. Capture data were analysed using a classical approach and a spatially-explicit approach (SECR), while count data were analysed with N-mixture models. Results show that classical capture analyses yield a lower abundance, while SECR and N-mixture models give similar and higher estimates. An optimization of the sampling design for studies regarding birds` abundance and species-habitat relationship should consider the use of point counts for song/visual detection of individual birds while fitting N-mixture models for abundance estimation.